Dimensions of Qur'anic Exegesis in the Repetition of Surah Al-Qamar Verses 17, 22, 32, And 40: A Perspective from Ibn Kathir's Tafsir - Ahmad Zaky Ramadhan (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
The repetition of Qur'anic verses (takrār al-ayat) is one of the distinctive rhetorical features of the Qur'an, reflecting profound meanings, wisdom, and communicative purposes. One of the most significant examples appears in Surah Al-Qamar verses 17, 22, 32, and 40 through the repeated statement, "Wa laqad yassarna al-Qur'ana li al-dhikri fa hal min muddakir" ("Indeed, we have made the Qur'an easy for remembrance, so is there anyone who will take heed?"), which occurs four times within the same surah. This study aims to examine the meaning of taisīr, analyze the function of the repeated taisīr verse, and construct the dimensions of Qur'anic taisīr from the perspective of Ibn Kathir's exegesis. This research employs a qualitative library research approach using the tahlili (analytical) method of Qur'anic exegesis combined with content analysis. Primary data were obtained from the Qur'an and Tafsīr al-Qur'ān al-'Aẓīm by Ibn Kathir, while secondary data were collected from classical works on 'Ulūm al-Qur'ān, Qur'anic commentaries, and relevant scholarly publications. Data collection was conducted through documentation studies, followed by verse identification, linguistic analysis, contextual interpretation, comparative examination of exegetical views, thematic classification, and inductive interpretation. The findings reveal that, according to Ibn Kathir, taisīr extends beyond the ease of reciting and memorizing the Qur'an to include the ease of understanding, contemplating, and receiving divine guidance from its teachings. The repeated verse functions as theological affirmation, rhetorical reinforcement, a means of Qur'anic exhortation, thematic cohesion within the surah, and a reflective invitation for humanity to learn from the history of previous nations. Furthermore, this study formulates five dimensions of Qur'anic taisīr: theological, linguistic, rhetorical, epistemological, and da'wah dimensions.